Extraction of Viral Nucleic Acids with Carbon Nanotubes Increases SARS-CoV-2 Quantitative Reverse Transcription Polymerase Chain Reaction Detection Sensitivity - Jeong, Sanghwa (ACS Nano, 2021)
The global SARS-CoV-2 coronavirus pandemic has led to a surging demand for rapid and efficient viral infection diagnostic tests, generating a supply shortage in diagnostic test consumables including nucleic acid extraction kits. Here, we develop a modular method for high-yield extraction of viral single-stranded nucleic acids by using ‘capture’ ssDNA sequences attached to carbon nanotubes. Target SARS-CoV-2 viral RNA can be captured by ssDNA-nanotube constructs via hybridization and separated from the liquid phase in a single-tube system with minimal chemical reagents, for downstream quantitative reverse transcription polymerase chain reaction (RT-qPCR) detection. This nanotube-based extraction method enables 100% extraction yield of target SARS-CoV-2 RNA from phosphate buffered saline in comparison to ~20% extraction yield when instead using a commercial silica-column kit. Notably, carbon nanotubes enable extraction of nucleic acids directly from 50% human saliva with similar efficiency as achieved with commercial DNA/RNA extraction kits, thereby bypassing the need for further biofluid purification and avoiding the use of commercial extraction kits. Carbon nanotube-based extraction of viral nucleic acids facilitates high-yield and high-sensitivity identification of viral nucleic acids such as the SARS-CoV-2 viral genome with reduced reliance on reagents affected by supply chain obstacles.